Oral Health Status of Disabled Individuals Attending Special Schools - Altun, Ceyhan (Dental Investigations Society, 2010)
OBJECTIVES: The purpose of this study was to determine the prevalence of the dmft-DMFT indexes and the oral hygiene status of 136 individuals attending a special school for the disabled. METHODS: Participants were grouped according to disability [Mental Retardation (MR), Cerebral Palsy (CP), Autistic Disorder (AD), Down Syndrome (DS), Other (OTH)] and age [2–6 years (n=24), 7–12 years (50 children) and 13+ years (62 children]. Caries examinations were carried out in accordance with WHO criteria and oral cleanliness was evaluated by visually assessing the presence of plaque on teeth. RESULTS: The age range of patients was 2–26 years (mean age: 11.89±5.19 years). Mean dmft and DMFT scores by age group were as follows: 2–6 years: dmft=2.04±2.24; 7–12 years: dmft=2.24±2.60, DMFT=0.98±2.58; 13+years: DMFT=2.68±2.91. Overall, 15.4% of children had no caries or fillings. While dmft and DMFT levels (P>.05) did not vary significantly by type of disability, oral cleanliness did. Children with autism were observed to maintain the best oral hygiene and those with mental retardation (MR), the poorest. CONCLUSIONS: It is important for the dentist to concentrate on a preventive approach and provide proper dental education to parents of disabled individuals. Among the children with disabilities, more attention should be paid to the oral hygiene of MR group.